Sonographic Evaluation of the Plantar Heel in Asymptomatic Endurance Runners. (11th September 2015) - Hall, Mederic M.; Finnoff, Jonathan T.; Sayeed, Yusef A.; Smith, Jay
Abstract : Objectives: The primary purpose of this investigation was to determine the prevalence and spectrum of asymptomatic sonographically determined structural changes in the plantar fascia and plantar heel pad among experienced runners without a history of heel pain. Methods: Thirty‐nine asymptomatic runners without a history of plantar heel pain were recruited. The following sonographic measures were recorded: power Doppler sonography in the plantar heel pad and plantar fascia, echo texture of the plantar heel pad, uncompressed heel pad thickness, compressed heel pad thickness, heel pad compressibility index, plantar fascia thickness, and plantar fascia echo texture. Results: Doppler flow was shown in the plantar heel pads of 88% (68 of 77) of heels and 92% (36 of 39) of runners. Heel pad echo texture abnormalities were found in 86% (66 of 77) of heels and 97% (38 of 39) of runners. Mean values for right and left uncompressed heel pad thickness were 13.8 and 13.7 mm, respectively. The mean heel pad compressibility indices were 0.51 for the right heel and 0.53 for the left heel. Eight percent (6 of 77) of fat pads in 10% (4 of 39) of runners had abnormal compressibility indices. Doppler flow was present in the plantar fascia in 31% (24 of 77) of heels and 44% (17 of 39) of runners. The mean plantar fascia thicknesses were 3.78 mm for the right and 3.87 mm for the left. Forty‐eight percent (37 of 77) of heels had an abnormal plantar fascia echo texture. Conclusions: At least 1 potentially abnormal sonographic finding was present in each heel of all asymptomatic runners in this study. Consequently, sonographic abnormalities in the plantar heel should be interpreted within the clinical context when evaluating runners.